Influence Analysis of Cleft Type and Supernumerary Teeth Eruption in the Prognosis of Bone Graft in Patients With Cleft Palate - Gaujac, Cristiano [UNESP]; Souza Faco, Eduardo Francisco de [UNESP]; Shinohara, Elio Hitoshi [UNESP]; Souza Faco, Renato Andre de; Pereira, Flavia Priscila [UNESP]; Assunção, Wirley Goncalves [UNESP] (Lippincott Williams & Wilkins, 2014)
Objective: The aim of this study was to investigate the influence of cleft type and supernumerary tooth eruption on the treatment of palatal clefts with alveolar bone grafts.Materials and Methods: In this article, medical records of 40 patients with palatal clefts and associated supernumerary teeth who were treated with alveolar bone grafting in the Hospital for Craniofacial Anomalies Rehabilitation were assessed. The patients were studied to assess the influence of supernumerary teeth and the cleft severity on the prognosis of the alveolar bone graft.Results: Forty medical records were included in the assessment. When the teeth in the cleft had an anatomic shape close to canine, we called them precanine. When they were very small or malformed, we called them anomalous lateral incisors. The teeth studied showed good prognoses and were more expressive in the preforaminal clefts (87.5%) than in the transforaminal ones (62.5%). Moreover, the transforaminal clefts presented a higher percentage in satisfactory and poor prognoses (37.5%). The authors found that supernumerary teeth influenced the maintenance of alveolar bone graft height and that transforaminal clefts presented a worse prognosis than preforaminal clefts.
Keywords: Cleft palate; bone graft; supernumerary teeth; treatment